Bringing the Global to the Local: the challenges of multi-level governance for global policy implementation in Africa. Issue 3 (2nd September 2021) - Croese, Sylvia; Oloko, Michael; Simon, David; Valencia, Sandra C.
ABSTRACT: The New Urban Agenda (NUA) and Agenda 2030's Sustainable Development Goals (SDGs) recognise the key role of 'sub-national entities', including cities, in achieving sustainable development. However, since these global policy agendas were agreed and signed by national governments, implementing them at the local level requires a process of localisation to fit local realities. This paper analyses the national guidance (or lack of) and the resultant collaborations emerging between various levels of government in the implementation of these agendas in African cities, namely Kisumu, Kenya and Cape Town, South Africa. It argues that effective implementation of the SDGs requires a strong framework for multi-stakeholder engagement and coordination at all levels of governance, which is possible if both top-down and bottom-up approaches are used concurrently and harmonised.